2013
DOI: 10.1097/moo.0b013e32835ac656
|View full text |Cite
|
Sign up to set email alerts
|

Osteitis and paranasal sinus inflammation

Abstract: Osteitis is more often present in patients with extended radiological disease and in patients undergoing revision surgery. More studies are necessary regarding its management, clinical implications, and natural course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 22 publications
2
28
0
2
Order By: Relevance
“…Of note, previous surgery has been associated with worsened osteitis scores in several studies, suggesting osteitis may be a marker of more severe disease and/or possibly a reaction to previous surgery. 386,399,401,402 The causality and relationship of bacterial biofilms, mucosal pathology, and bacterial infection is not well understood in relationship to osteitis. Bacterial infection of the bone is an unlikely cause of osteitis in CRS patients.…”
Section: S55mentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, previous surgery has been associated with worsened osteitis scores in several studies, suggesting osteitis may be a marker of more severe disease and/or possibly a reaction to previous surgery. 386,399,401,402 The causality and relationship of bacterial biofilms, mucosal pathology, and bacterial infection is not well understood in relationship to osteitis. Bacterial infection of the bone is an unlikely cause of osteitis in CRS patients.…”
Section: S55mentioning
confidence: 99%
“…401 Single photon emission CT (SPECT) has been suggested as another modality, but is costly, not readily available, and exposes the patient to larger doses of radiation. 401,402 A variety of grading systems using CT imaging have also been proposed, including the Kennedy Osteitis Score, Global Osteitis Scoring Scale (GOSS), scoring based upon Hounsfield units (HU), thickness of bony partitions, as well as systematic examinations of separate reference points in the sinuses. 387,389,392,403,404 As with diagnostic testing for osteitis, these grading systems have not been standardized.…”
Section: S55mentioning
confidence: 99%
See 1 more Smart Citation
“…Osteitis has been recognized as a potential confounding factor in the outcome of CRS treatment. Numerous studies have found an association between the presence of severe osteitis and disease extension using endoscopic scores such as the Lund-Mackay score [33,35,36]. However, no significant differences have been found in the quality of life in patients with and without osteitis [33,35].…”
Section: Extent Of Disease At Baseline and Comorbiditiesmentioning
confidence: 97%
“…On the CT scan, the osteitic bone appears as heterogeneous, irregular bone with areas of growth and destruction [35]. Osteitis has been recognized as a potential confounding factor in the outcome of CRS treatment.…”
Section: Extent Of Disease At Baseline and Comorbiditiesmentioning
confidence: 99%